THE TRUE COST OF TECHNOLOGY: DOUBLE EXTRACTIVISM AND GREEN CRIMINOLOGY IN SERBIA - Ivana Stepanović (Revija za kriminologiju i krivično pravo)
The socalled green transition that relies on batterypowered technology dramatically raises demands for lithium and other minerals. The same resources are used to produce batteries for phones, computers, electric cars, and other devices with internet connectivity that simultaneously extract personal data. While research projects in natural sciences warn of ecological and human health implications of extracting minerals, social sciences emphasise the dangers of electronic transparency. The true cost of green transition and digitalisation turns out to be very high, especially because these processes are based on the extraction of both material resources and behavioural data. This paper argues that the mining of lithium and other minerals is not a local or national issue, but rather an international concern. Using concept analysis and digital ethnography, it analyses lithium mining narratives in Serbia and challenges the idea of “green transition” with notions of double extractivism and digital and green criminology.